Nanocrystalline Electrodeposited Fe-W/Al2O3 Composites: Effect of Alumina Sub-microparticles on the Mechanical, Tribological, and Corrosion Properties - Nicolenco, Aliona; Mulone, Antonio; Imaz, Naroa; Tsyntsaru, Natalia; Sort, Jordi; Pellicer, Eva; Klement, Uta; Cesiulis, Henrikas; García-Lecina, Eva (Frontiers in Chemistry, 2019)
In this study, nanocrystalline Fe-W alloy and Fe-W/Al2O3 composite coatings with various contents of submicrosized alumina particles have been obtained by electrodeposition from an environmentally friendly Fe(III)-based electrolyte with the aim to produce a novel corrosion and wear resistant material. The increase in volume fraction of Al2O3 in deposits from 2 to 12 % leads to the grain refinement effect, so that the structure of the coatings changes from a nanocrystalline to amorphous-like with grain sizes below 20 nm. Nevertheless, the addition of particles to the Fe-W matrix does not prevent the development of a columnar structure revealed for all the types of studied coatings. The observed reduction in both hardness and elastic modulus of the Fe-W/Al2O3 composites is attributed to the apparent grain size refinement/amorphization and the nanoporosity surrounding the embedded Al2O3 particles. In the presence of 12 vol% of Al2O3 in deposits the wear rate decreases by a factor of 10 as compared to Fe-W alloy tested under dry friction conditions due to the lowering of tribo-oxidation. The addition of alumina particles slightly increases the corrosion resistance of the coatings; however, the corrosion in neutral chloride solution occurs through the preferential dissolution of Fe from the matrix. The obtained results provide a possibility to integrate the nanocrystalline Fe-W/Al2O3 composite coatings into various systems working under dry friction conditions, for example, in high-temperature vacuum systems.